Dynamics of Pluralism in Santri Education: Perspectives and Practices in Modern Islamic Boarding Schools - Ma'rufah, Afni (IJoIS: Indonesian Journal of Islamic Studies, 2024)
One of the main foundations in maintaining diversity and harmony in Indonesia's multicultural society is pluralism. Islamic boarding schools as Islamic educational institutions have an important role in instilling pluralism values in students, especially in the era of modern Islamic boarding schools that are more open to social dynamics. However, the application of the principle of pluralism in Islamic boarding schools still faces various challenges, especially in maintaining a balance between strict religious teachings and acceptance of diverse values. This study examines the dynamics of the application of pluralism in student education in modern Islamic boarding schools, focusing on the perspectives and practices applied. The method used in this study is a literature study, where various literature that discusses pluralism education, student character, and educational models in modern Islamic boarding schools are comprehensively analyzed. The results of the study show that modern Islamic boarding schools have implemented several strategies to integrate pluralism values into the curriculum and educational activities. This is done through an inclusive learning approach, interfaith dialogue, and the formation of an attitude of tolerance among students. However, there are still challenges in the implementation of pluralism, especially related to the resistance of some conservative groups and limited resources. This study concludes that despite facing various obstacles, pluralism education in modern Islamic boarding schools has significant potential in forming the character of students who are tolerant and open to differences.